Current and future directions in Belgian medical and health sciences librarianship: a user‐tailored approach. (2nd November 2018) - De Meulemeester, Ann; Schietse, Bérengère; Vermeeren, Bruno; Ghesquière, Elke; Declève, Ghislaine; Buysse, Heidi; Discart, Inge; Alewaeters, Katrien; Durieux, Nancy; Peleman, Renaat; Pauwels, Nele
Abstract: This article is part of a new series in this regular feature. The series intend to serve as a road map by sharing expertise and drawing together trends that are relevant to both health science librarians and health informatics professionals. The present article is a collaboration of six medical and health sciences libraries in Belgium and the Flemish library and archive association (VVBAD, n.d., https://www.vvbad.be/ ). It aims to elucidate the extended, user‐tailored approach provided by medical and health sciences libraries in Belgium motivated by the recent changes in user expectations and behaviour.